Challenges of implementation and implementation research: Learning from an intervention study designed to improve tumor registry reporting. (27th August 2016) - McAlearney, Ann Scheck; Walker, Daniel M; Livaudais-Toman, Jennifer; Parides, Michael; Bickell, Nina A
Objectives: Implementation of interventions designed to improve the quality of medical care often proceeds differently from what is planned. Improving existing conceptual models to better understand the sources of these differences can help future projects avoid these pitfalls and achieve desired effectiveness. To inform an adaptation of an existing theoretical model, we examined unanticipated changes that occurred in an intervention designed to improve reporting of adjuvant therapies for breast cancer patients at a large, urban academic medical center. Methods: Guided by the complex innovation implementation conceptual framework, our study team observed and evaluated the implementation of an intervention designed to improve reporting to a tumor registry. Findings were assessed against the conceptual framework to identify boundary conditions and modifications that could improve implementation effectiveness. Results: The intervention successfully increased identification of the managing medical oncologist and treatment reporting. During implementation, however, unexpected external challenges including hospital acquisitions of community practices and practices' responses to government incentives to purchase electronic medical record systems led to unanticipated changes and associated threats to implementation. We present a revised conceptual model that incorporates the sources of these unanticipated challenges. Conclusion: This report of our experience highlights the importance of monitoring implementation over time and accounting for changes that affect both implementation and measurement of intervention impact. In this article, we use our study to examine the challenges of implementation research in health care, and our experience can help future implementation efforts.